Association of polymorphic variants rs6684209 and rs7521023 of the calsequestrin gene (CASQ2) with contractile myocardial function in patients with coronary artery disease - E. F. Muslimova; T. Yu. Rebrova; E. A. Archakov; D. S. Kondratieva; Yu. G. Lugacheva; R. E. Batalov; S. A. Afanasiev (Российский кардиологический журнал)
Aim. To study the association between polymorphic rs6684209 and rs7521023 variants of the CASQ2 gene and myocardial contractile function and risk factors for the development of chronic heart failure (CHF).Material and methods. The study included 172 patients with CHF developing on the background of coronary artery disease. We identified polymorphic variants rs6684209 and rs7521023 of the CASQ2 gene by real-time polymerase chain reaction.Results. There was no association of the rs6684209 variant with CHF and the frequency of cardiac arrhythmias. It was revealed that the carriage of the GG genotype of rs7521023 variant is associated with a higher frequency of dilatation of the left atrium (p=0,044) and an increased end-systolic volume (p=0,045).Conclusion. Among patients with coronary artery disease, there was no correlation between the rs7521023 and rs6684209 variants of the calsequestrin gene (CASQ2) with the frequency of cardiac arrhythmias. There was no association of the rs6684209 variant with CHF risk factors and parameters of myocardial contractile function. A relationship was found between the GG genotype of the rs7521023 variant and a higher frequency of left atrium dilatation. Among patients taking beta-blockers, the GG genotype is associated with an increase in end-systolic volume.